The Role of Celebrity Endorsement in Fashion Product Purchasing Decisions at Shopee: A Qualitative Review - Gracedelia Jeanywealsny Ngasa; Laurensius Sandrio; Septian Hutagalung; Irna Karina Josephine Kaban (Jurnal Penelitian Terapan Mahasiswa, 2025)
This study aims to examine the effect of celebrity endorsement on purchasing decisions for fashion products on the Shopee e-commerce platform. The research method used is a qualitative approach with non-probability sampling technique. Data was collected through in-depth interviews with Shopee consumers who have experience buying fashion products endorsed by celebrities. The results showed that celebrity endorsement plays a significant role in attracting consumer attention and building trust in the promoted product, which ultimately increases consumer purchase intention. The relationship between fans and celebrities is a key factor in influencing purchasing preferences and behavior. In addition, Shopee as an e-commerce platform also supports increased sales through various attractive features and promotions. This research provides valuable insights for marketers in developing more effective and consumer-oriented marketing strategies in today's digital era.